2017
DOI: 10.1002/adma.201605050
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Inspired Bright Structurally Colored Colloidal Amorphous Array Enhanced by Controlling Thickness and Black Background

Abstract: Inspired by Steller's jay, which displays angle-independent structural colors, angle-independent structurally colored materials are created, which are composed of amorphous arrays of submicrometer-sized fine spherical silica colloidal particles. When the colloidal amorphous arrays are thick, they do not appear colorful but almost white. However, the saturation of the structural color can be increased by (i) appropriately controlling the thickness of the array and (ii) placing the black background substrate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 31 publications
(24 reference statements)
5
141
0
Order By: Relevance
“…Angleindependent structural colors appear matte and homogeneous, often indistinguishable from colors that come from absorbing pigments. This type of coloration is found in many species of birds [2][3][4][5][6][7][8][9] and has been mimicked in disordered assemblies of colloidal particles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 91%
“…Angleindependent structural colors appear matte and homogeneous, often indistinguishable from colors that come from absorbing pigments. This type of coloration is found in many species of birds [2][3][4][5][6][7][8][9] and has been mimicked in disordered assemblies of colloidal particles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 91%
“…A large area of uniform PAS membranes was obtained by depositing alternating layers of charged colloidal particles and layers of an oppositely charged polyelectrolyte. 76 By using nonuniform particles for the colloidal assembly, the tendency for colloidal crystallization during the selfassembly process could be considerably suppressed, which favors the formation of 3D PASs. In this regard, Lai et al 77 dispersed nonuniform SiO 2 particles constructing a photocurable PAS resin in the resin prepolymer.…”
Section: Amorphous Colloidal Arraysmentioning
confidence: 99%
“…As a result, stimuli‐responsive, structural color materials can be created . Additionally, understanding the coloring mechanisms of these color materials has clearly shown that the background color is also important for creating colorful color materials . Generally, additive and subtractive color mixing reproduce colors.…”
mentioning
confidence: 99%
“…When the background was white, the reflection intensity from the background was high for the entire visible region, and the PBG due to the Bragg reflection from the colloidal crystals could not be observed in the spherical colloidal crystal reflection spectra (Figure b). [4a] As a result, observing the structural color arising from the spherical colloidal crystals was difficult, and the spherical colloidal crystals appeared as a white powder. For the reflection spectra measured with a black background, the influence of the background light disappeared, and the PBG was clearly observed (Figure c).…”
mentioning
confidence: 99%
See 1 more Smart Citation